2017
DOI: 10.14449/jbd.2017.5.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Re-Excision Rate in Breast Conservation Surgery after Neoadjuvant Chemotherapy

Abstract: The purpose of this study was to compare the success rate of re-excision and breast-conserving surgery (BCS) between patients who received neoadjuvant chemotherapy and those who did not. Methods: In this retrospective cohort study, 256 women who had clinical T2 breast cancer and planned to receive, as initial treatment either BCS (n= 197) or neoadjuvant chemotherapy (n= 59) between January 2009 and December 2012 were included. The data, including age, initial tumor size, mammographic microcalcification, ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In the NACT setting, no standard approach to breast conservation and margin interpretation has been delineated. There are conflicting reports about whether NACT is associated with lower [2, 15] or higher [16] rates of re-excision following lumpectomy. We found that preopRT was associated with higher rates of positive surgical margins (8.2% vs 4.2%).…”
Section: Discussionmentioning
confidence: 99%
“…In the NACT setting, no standard approach to breast conservation and margin interpretation has been delineated. There are conflicting reports about whether NACT is associated with lower [2, 15] or higher [16] rates of re-excision following lumpectomy. We found that preopRT was associated with higher rates of positive surgical margins (8.2% vs 4.2%).…”
Section: Discussionmentioning
confidence: 99%